Body mass index and early CD4 T‐cell recovery among adults initiating antiretroviral therapy in North America, 1998–2010. Issue 9 (11th May 2015) - Koethe, JR; Jenkins, CA; Lau, B; Shepherd, BE; Silverberg, MJ; Brown, TT; Blashill, AJ; Anema, A; Willig, A; Stinnette, S; Napravnik, S; Gill, J; et al.
<x xml:space="preserve">Abstract</x> Objectives Adipose tissue affects several aspects of the cellular immune system, but prior epidemiological studies have differed on whether a higher body mass index (BMI) promotes CD4 T‐cell recovery on antiretroviral therapy (ART). The objective of this analysis was to assess the relationship between BMI at ART initiation and early changes in CD4 T‐cell count. Methods We used the North American AIDS Cohort Collaboration on Research and Design (NA‐ACCORD) data set to analyse the relationship between pre‐treatment BMI and 12‐month CD4 T‐cell recovery among adults who started ART between 1998 and 2010 and maintained HIV‐1 RNA levels < 400 copies/mL for at least 6 months. Multivariable regression models were adjusted for age, race, sex, baseline CD4 count and HIV RNA level, year of ART initiation, ART regimen and clinical site. Results A total of 8381 participants from 13 cohorts contributed data; 85% were male, 52% were nonwhite, 32% were overweight (BMI 25–29.9 kg/m2) and 15% were obese (BMI > 30 kg/m2). Pretreatment BMI was associated with 12‐month CD4 T‐cell change (P < 0.001), but the relationship was nonlinear (P < 0.001). Compared with a reference of 22 kg/m2, a BMI of 30 kg/m2 was associated with a 36 cells/μL [95% confidence interval (CI) 14, 59 cells/μL] greater CD4 T‐cell count recovery among women and a 19 cells/μL (95% CI 9, 30 cells/μL) greater recovery among men at 12 months. At a BMI > 30 kg/m2, the observed benefit was attenuated among men to a greater degree than among women, although this difference was not statistically significant. Conclusions A BMI of approximately 30 kg/m2 at ART initiation was associated with greater CD4 T‐cell recovery at 12 months compared with higher or lower BMI values, suggesting that body composition may affect peripheral CD4 T‐cell recovery.